2011
DOI: 10.1051/0004-6361/201116530
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic coupling of planets and small bodies with a pulsar wind

Abstract: Aims. We investigate the electromagnetic interaction of a relativistic stellar wind with a planet or a smaller body in orbit around the star. This may be relevant to objects orbiting a pulsar that are expected to hold a planetary system, such as PSR B1257+12 and PSR B1620-26, or to pulsars with suspected asteroids or comets. Methods. We extend the theory of Alfvén wings to relativistic winds. Results. When the wind is relativistic but slower than the total Alfvén speed, a system of electric currents carried by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…The factor Σ A is the Alfvén wing conductance. Mottez & Heyvaerts (2011b) have shown that for a highly relativistic Poynting-flux-dominated wind, as expected around pulsars,…”
Section: Alfvén Wings and Associated Electric Currentsmentioning
confidence: 99%
See 4 more Smart Citations
“…The factor Σ A is the Alfvén wing conductance. Mottez & Heyvaerts (2011b) have shown that for a highly relativistic Poynting-flux-dominated wind, as expected around pulsars,…”
Section: Alfvén Wings and Associated Electric Currentsmentioning
confidence: 99%
“…Mottez & Heyvaerts (2011b) have shown than in cold ideal magneto-hydrodynamic Poyntingflux-dominated winds, where the models show that asymptotically γ ∞ ∼ σ 1/3 0 , the wind is sub-Aflvénic, in the sense defined above, at any distance. But if γ ∞ ∼ σ a 0 , and a > 1/3, a transition from sub-Alfvénic to super-Alfvénic wind occurs at a finite distance.…”
Section: Possible Location Of the Fast-mode Critical Surfacementioning
confidence: 99%
See 3 more Smart Citations